2023
DOI: 10.3390/ijms242115988
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4-Allele in Middle-Aged and Older Autistic Adults: Associations with Verbal Learning and Memory

Samantha A. Harker,
Lamees Al-Hassan,
Matthew J. Huentelman
et al.

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disability and recent evidence suggests that autistic adults are more likely to develop Alzheimer’s disease (Alz) and other dementias compared to neurotypical (NT) adults. The ε4-allele of the Apolipoprotein E (APOE) gene is the strongest genetic risk factor for Alz and negatively impacts cognition in middle-aged and older (MA+) adults. This study aimed to determine the impact of the APOE ε4-allele on verbal learning and memory in MA+ autistic adults (ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…In this review, most studies confirmed diagnosis following DSM-IV ( Braden et al, 2017 ; Davids et al, 2016 ; Geurts et al, 2020 ; Groenman et al, 2024 ; Groot et al, 2021 ; Lever and Geurts, 2016 ; Spek et al, 2017 ; Torenvliet et al, 2023b , 2024 ; Tse et al, 2019 ), DSM-5 ( Braden et al, 2017 ; Davids et al, 2016 ; Groenman et al, 2024 ; Groot et al, 2021 ; Harker et al, 2023 ; Kohli et al, 2019 ; Pagni et al, 2022 ; Torenvliet et al, 2022 , 2023a , 2023b , 2024 ; Tse et al, 2019 ; Walsh et al, 2022 ), or NICE guidelines for the diagnosis and management of autistic adults ( https://www.nice.org.uk/guidance/cg142 ) ( Koolschijn and Geurts, 2016 ; Koolschijn et al, 2017 ). In confirming diagnosis, the Autism Diagnostic Observation Schedule (ADOS) was used by the majority of selected studies ( Braden et al, 2017 ; Davids et al, 2016 ; Groot et al, 2021 ; Harker et al, 2023 ; Kohli et al, 2019 ; Koolscjihn & Geurts, 2016 ; Koolschijn et al, 2017 ; Lever et al, 2016 ; Powell et al, 2017 ; Pagni et al, 2022 ; Torenvliet et al, 2022 ; Walsh et al, 2022 ), with some of the studies using ADOS in addition to screening instruments such as the Autism Spectrum Quotient (AQ) ( Bathelt et al, 2022 ; Groenman et al, 2024 ; Groot et al, 2021 ; Koolschijn and Geurts, 2016 ; Koolschijn et al, 2017 ; Lever and Geurts, 2016 ; Torenvliet et al, 2023a , 2023b , 2024 ) or Social Responsiveness Scale (SRS) ( Braden et al, 2017 ; Pagni et al, 2022 ; Powell et al, 2017 ;…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…In this review, most studies confirmed diagnosis following DSM-IV ( Braden et al, 2017 ; Davids et al, 2016 ; Geurts et al, 2020 ; Groenman et al, 2024 ; Groot et al, 2021 ; Lever and Geurts, 2016 ; Spek et al, 2017 ; Torenvliet et al, 2023b , 2024 ; Tse et al, 2019 ), DSM-5 ( Braden et al, 2017 ; Davids et al, 2016 ; Groenman et al, 2024 ; Groot et al, 2021 ; Harker et al, 2023 ; Kohli et al, 2019 ; Pagni et al, 2022 ; Torenvliet et al, 2022 , 2023a , 2023b , 2024 ; Tse et al, 2019 ; Walsh et al, 2022 ), or NICE guidelines for the diagnosis and management of autistic adults ( https://www.nice.org.uk/guidance/cg142 ) ( Koolschijn and Geurts, 2016 ; Koolschijn et al, 2017 ). In confirming diagnosis, the Autism Diagnostic Observation Schedule (ADOS) was used by the majority of selected studies ( Braden et al, 2017 ; Davids et al, 2016 ; Groot et al, 2021 ; Harker et al, 2023 ; Kohli et al, 2019 ; Koolscjihn & Geurts, 2016 ; Koolschijn et al, 2017 ; Lever et al, 2016 ; Powell et al, 2017 ; Pagni et al, 2022 ; Torenvliet et al, 2022 ; Walsh et al, 2022 ), with some of the studies using ADOS in addition to screening instruments such as the Autism Spectrum Quotient (AQ) ( Bathelt et al, 2022 ; Groenman et al, 2024 ; Groot et al, 2021 ; Koolschijn and Geurts, 2016 ; Koolschijn et al, 2017 ; Lever and Geurts, 2016 ; Torenvliet et al, 2023a , 2023b , 2024 ) or Social Responsiveness Scale (SRS) ( Braden et al, 2017 ; Pagni et al, 2022 ; Powell et al, 2017 ;…”
Section: Resultsmentioning
confidence: 76%
“…Twenty-two studies were selected. A summary of extracted data is shown in Table 1 for cognitive studies ( Bathelt et al, 2022 ; Davids et al, 2016 ; Geurts et al, 2020 ; Geurts and Vissers, 2012 ; Groenman et al, 2024 ; Groot et al, 2021 ; Harker et al, 2023 ; Klein et al, 2023 ; Lever and Geurts, 2016 ; Powell et al, 2017 ; Spek et al, 2017 ; Torenvliet et al, 2022 , 2023a , 2023b , 2024 ; Tse et al, 2019 ) and Table 2 for brain imaging studies ( Braden et al, 2017 ; Kohli et al, 2019 ; Koolschijn et al, 2017 ; Koolschijn and Geurts, 2016 ; Pagni et al, 2022 ; Walsh et al, 2022 ) Twenty-one studies [except for Klein et al, (2023) ] included more male than female participants, of which two cognitive ( Geurts et al, 2020 ; Spek et al, 2017 ) and one imaging article ( Braden et al, 2017 ) only recruited male participants. All studies focused on autistic adults without intellectual disability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations